On the Oxidation State of Cu2O upon Electrochemical CO2 Reduction: An XPS Study. Issue 22 (31st July 2019) - Permyakova, Anastasia A.; Herranz, Juan; El Kazzi, Mario; Diercks, Justus S.; Povia, Mauro; Mangani, Léa Rose; Horisberger, Michael; Pătru, Alexandra; Schmidt, Thomas J.
Abstract: The encouraging selectivity of copper oxides for the electroreduction of CO2 into ethylene and alcohols has led to a vivid debate on the possible relation between their operando (sub‐)surface oxidation state (i. e. fully reduced or partially oxidized) and this distinct reactivity. The high roughness of the Cu oxides used in previous studies on this matter adds complexity to this controversy and motivated us to prepare quasi ‐planar Cu2 O thin films that displayed a CO2 reduction selectivity similar to that of oxide‐derived copper catalysts reported in previous studies. Most importantly, when the post‐mortem thin films were transferred for characterization in an air‐free environment, X‐ray photoelectron spectroscopy measurements confirmed their complete reduction in the course of the CO2 reduction reaction. Thus, our results indicate that the selectivity of the Cu oxides featured in previous studies stems from their enhanced roughness, highlighting the importance of controlled sample transfer upon post‐mortem characterization with ex situ techniques. Abstract : How did they get here ? X‐ray photoelectron spectroscopy of post‐mortem Cu2 O thin film electrodes characterized following an air‐free transfer to ultra‐high vacuum unveils their complete transformation into Cu 0 in the course of CO2 electroreduction.